Crypto Currency Trading in Islam: An Attempt to Explore the Law amidst Technological Advances - Sujono, Imam; Rochman, Muhammad Habibur; Mu'ala, Abdulloh Afifil (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study aims to find out how the crypto trading law and the status of money generated from the trading results. This study uses a normative legal method with a descriptive analysis approach. Legal materials are obtained from the Bahtsul Masail decision of PWNU East Java, Bahtsul Masail with PWNU in Yogyakarta, and Bahtsul Masail Islamic Law Firm. The results of the study show that trading crypto is permitted by Islamic law as long as there is no gharar. This study implies that people who trade crypto must have sufficient knowledge about crypto currency.